PLANKTON AND BENTHOS DISTRIBUTION OF RIVER DONGA, TARABA STATE, NORTH EAST, NIGERIA - Igbani Flourizel, (International Journal For Research In Agricultural And Food Science, 2023)
A twelve (12) week investigation was carried out in River Donga, to determine the plankton and benthos distribution and abundance. Three sections of the River were sampled and human activities were considered in the choice of sampling stations. A total of thirty three (33) individual species of plankton and benthos were identified; sixteen (16) individual species belonging to phytoplanktons were harvested, eleven (11) individual species belonging to zooplanktons were harvested, while six (6) individual species belonging to benthos were also harvested in stations A, B and C respectively. They comprised of 31 families and 26 orders; the highest harvested individual species was C. radiates (100 species), while the least harvested individual species was A. lumbricoide (1 species). A total of 881 species of plankton and benthos were harvested 524 species (59.48%) belonging to phytoplanktons; 299 species (33.94%) belonging to zooplanktons were recorded, while 58 species (6.58%) belonging to benthos were also recorded. Analysis of variance (ANOVA P<0.05), Fisher’s Least Significant Difference (FLSD) and Pearson’s Correlation P<0.01 were used to test significant levels. The highest temperature value was (29.0±1.36ºC) in Station A; the least was (27.9±0.6 ºC) in station B. The highest Dissolved Oxygen was (8.08±0.22mg/L) in station B; the least was (7.32±0.5mg/L) in station A. The mean pH values were slightly acidic; the highest value was (6.71±0.62) in station A; the least value was (6.27±0.27) in station C. Electrical conductivity, though, the highest value was (16.07±0.25µs/cm) in Station C; the least was (15.58±0.52µs/cm) in station A. The highest turbidity value was (33.25±6.15cm) in station A; the least value was (32.08±4.54cm) in station B. The highest total dissolved solid value was (0.36±0.38ppm) in Station C; the least was (0.24±0.32ppm) in station A. The river was highly productive in terms of its plankton and benthos richness; it was recommended that the physico-chemical characteristics of the researched ecosystem will aid the culture of edible frogs and fish. Nevertheless, monitoring of human activities and the conservation of its natural resources is key to a sustainable biodiversity for food sovereignty and security to better lives as climate change bites.